Clinical Practice Guidelines for Exogenous Poisoning. - Alexis Díaz Mesa; Eddy Pereira Valdés; Alba Enseñat Álvarez; Carlos Alberto Rodríguez Armada (Medisur)
Clinical Practice Guidelines for Exogenous Poisoning. Medical emergencies determined by the exposure to different substances (drugs, medicines, physical or chemical corrosive agents, etc). It includes the classification of toxic substances, clinical diagnosis (main syndromes), and description of therapeutic variations (vital support, antidotes, absorption measurements and increase of elimination and depuration of the toxic substance). It includes assessment guidelines focused on the most important aspects to be accomplished.